Сучасні методи визначення фальсифікації молока - Іщенко, Віра Миколаївна; Квітковська, Надія Петрівна; Костенко, Єлизавета Євгеніївна; Кочубей-Литвиненко, Оксана Валер'янівна; Іщенко, Микола Володимирович (My University, 2022)
У статті охарактеризовано способи фальсифікації молока, зокрема ті, які є най-складнішими для детектування. Розглянуто сучасні цільові фізико-хімічні методи виявлення фальсифікації молока, такі як високоефективна рідинна хроматогра-фія та газова хроматографія, масова спектрометрія із співвідношенням ізотопів, імуноферментний аналіз, ядерний магнітний резонанс і метод полімеразної реак-ції. Описано нецільові скринінгові методи: методи молекулярної абсорбційної та емісійної спектроскопії, спектроскопія ближньої ІЧ-області. Проведений аналітич-ний огляд розглянутих методів показав, що критеріями вибору того чи іншого методу повинна бути його придатність для досягнення поставленої мети, уні-версальність і чутливість аналізу, а також економічна доцільність використання. Milk is valuable for its special properties of protein, fat, vi-tamins, trace elements and should be included in the daily diet of a certain group of consumers. At the same time, products with a high nutritional value are the most vulnerable to falsification. The article analyzes the problem of falsification of food pro-ducts and, in particular, milk. An overview of the main types of milk falsification and the reasons that lead to it was carried out. Most often, milk adulteration is carried out by adding presserva-tives, diluting milk with water followed by adding substances with a high nitrogen content to compensate for the level of protein content, replacing milk fat with fat of vegetable origin, adding natural or dry whey to some dairy products, replacing one type of milk with another, in particular, reconstituted natural milk. The article notes that the issue of detecting adulteration of milk is extremely difficult, since the composition of milk is influen-ced by many factors: area and breed of livestock, climate and seasons, individual differences between animals, stages of lacta-tion, technological processes, etc. National food safety stan-dards were reviewed and modern physico-chemical methods for detecting milk adulteration were analyzed, in particular, targe-ted ones, such as high-performance liquid chromatography and gas chromatography, isotope ratio mass spectrometry, enzyme immunoassay, nuclear magnetic resonance, and the polymerase chain reaction method. Characterized non-targeted screening methods for detecting milk adulteration: methods of molecular absorption and emission spectroscopy, such as near-IR spectro-scopy, which, in combination with chemometric processing of the obtained data, can reliably establish milk adulteration. The need for the development of fast, inexpensive and effective analytical methods for detecting falsification and authenticity of milk is noted.
Keywords: кафедра харчової хімії; кафедра технології молока і молочних продуктів; молоко; фальсифікація; фізико -хімічний аналіз; milk; adulteration; physical and chemical analysis